2019
DOI: 10.24191/ajue.v15i3.7799
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Use Behaviour of Augmented Reality Technology Through Marlcardio: Adapting the Utaut Model

Abstract: Augmented reality (AR) is one type of learning process that can be applied through mobile learning known as mobile augmented reality. AR offers an innovative learning space through an active interaction of superimposing digital contents into the real context to enhance learning experiences. Previous studies have found that AR in education is able to lead students to achieve higher levels of engagement in the learning process. In contrast, the potential of AR in education has not been explored intensively. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 31 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Because, students show a higher level of participation and maintain a positive attitude (Durrington et al, 2006) when the online lectures are greatly interactive. Also, recent studies found that AR does increase the learners' engagement with the subject content (Nizar, Rahmat, Maaruf and Damio, 2019) AR-based presentations are also welcomed by the students due to their fun-filled content. Studies that compared AR presentations with traditional methods in education revealed that students want to go for an AR demonstration rather than a slide-based presentation (Di Serio, Báñez & Kloos, 2013).…”
Section: Related Workmentioning
confidence: 99%
“…Because, students show a higher level of participation and maintain a positive attitude (Durrington et al, 2006) when the online lectures are greatly interactive. Also, recent studies found that AR does increase the learners' engagement with the subject content (Nizar, Rahmat, Maaruf and Damio, 2019) AR-based presentations are also welcomed by the students due to their fun-filled content. Studies that compared AR presentations with traditional methods in education revealed that students want to go for an AR demonstration rather than a slide-based presentation (Di Serio, Báñez & Kloos, 2013).…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, research has suggested that pre-service and in-service teachers' beliefs and attitudes towards technology play an important role in the successful acceptance of any digital technologies in education (Teo, 2015). In this context, some AR studies have already examined the acceptance of MAR in teaching and learning by pre-service teachers (e.g., Cabero-Almenara et al, 2019;Nizar et al, 2019;Rahmat and Mohamad, 2021) and in-service teachers (e.g., Ibili et al, 2019;Jang et al, 2021), with most having used in their methodologies specific models and theories from social psychology and information systems fields, such as the Technology Acceptance Model (TAM) (Davis, 1989;Davis et al, 1989) and other modified versions of TAM, as well as the Unified Theory of Acceptance and Use of Technology model (UTAUT) (Venkatesh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, aside from the fact that there are relatively few studies on MAR acceptance by pre-service and in-service teachers, they too show certain limitations. Firstly, some acceptance models focus on investigating the acceptance of a particular application for a specific subject (e.g., Geometry, Cardiovascular disease, Geography) (e.g., Ibili et al, 2019;Nizar et al, 2019;Pasalidou & Fachantidis, 2021). Secondly, only a small number of previous studies have evaluated the extent to which the proposed models fit the data collected from their samples (Asiri & El-Aasar, 2022;Jang et al, 2021;Ma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papers with research questions that investigate the effect of AR on learning outcomes (N=123) [43][44][45][46][47]49,50,55,56,58,59,61,63,65, Papers with research questions that investigate the functionality of AR technology and its effectiveness (N=36) [47,48,51,52,57,62,108,123,133,148,150,[155][156][157]160,162,170,[176][177][178][179][180][181][182][183][184][185][186][187][188][189][190][191][192][193]…”
Section: Research Objectives Papersmentioning
confidence: 99%